Study protocol for the volume targeted mask ventilation versus pressure ventilation in preterm infants—the VOLT-trial - Law, Brenda H. Y.; Yaskina, Maryna; Davis, Peter G.; Polglase, Graeme; Dunn, Michael; Mukerji, Amit; Schmölzer, Georg M. (Frontiers in Pediatrics, 2026)
BackgroundThe rapid establishment of gas exchange after birth is vital for survival and long-term health. When newborn infants fail to initiate spontaneous breathing, positive pressure ventilation (PPV) is the cornerstone of respiratory support immediately after birth. The aim of PPV is to inflate the lungs, create a functional residual capacity, deliver an adequate tidal volume (VT), facilitate gas exchange, and stimulate breathing, without causing lung or brain injury. In the delivery room, PPV is routinely provided via a pressure-limited device (called a T-Piece resuscitator), where an arbitrary peak inflation pressure (PIP) is set, with the assumption an adequate and safe VT will be delivered. An alternative approach would be using a ventilator to deliver volume-targeted ventilation (VTV), whereby the PIP is adjusted to target a set VT measured by an inline flow sensor. While several trials have evaluated the use of respiratory function monitors to adjust the delivered VT during PPV, no trial has compared PPV with VTV-PPV in the delivery room.MethodsA randomized trial of VTV-PPV vs. PPV during neonatal resuscitation in preterm infants at birth to assess feasibility of a definitive trial for the intervention. Preterm infants born between 230/7 to 286/7 weeks' gestation will be eligible. Patients will be randomized to either the intervention (VTV-PPV) or the comparator (PPV) during respiratory support in the delivery room. The sample size will be 50 preterm infants. The primary outcome will be percentage of eligible participants (=infants requiring PPV) who have the intervention performed correctly without protocol deviation (=cross over to control group when randomized to VTV-group). Secondary outcomes will include neonatal morbidities (e.g., death, severe brain injury, bronchopulmonary dysplasia; and severe retinopathy of prematurity).DiscussionThe VOLT-trial aims to assess feasibility of VTV-PPV and will address gaps in the evidence regarding the optimal approach to the establishment of ventilation in the delivery room. We aim to use to results of this trial to inform the design of a large multi-centre trial.Study Protocol Registrationhttps://clinicaltrials.gov/study/NCT05144724, identifier NCT05144724.